2017
DOI: 10.3390/ijms18040812
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein Gene Family in the Sea Urchin Paracentrotus lividus: Gene Structure, Differential Expression and Phylogenetic Analysis

Abstract: Metallothioneins (MT) are small and cysteine-rich proteins that bind metal ions such as zinc, copper, cadmium, and nickel. In order to shed some light on MT gene structure and evolution, we cloned seven Paracentrotus lividus MT genes, comparing them to Echinodermata and Chordata genes. Moreover, we performed a phylogenetic analysis of 32 MTs from different classes of echinoderms and 13 MTs from the most ancient chordates, highlighting the relationships between them. Since MTs have multiple roles in the cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 77 publications
1
16
0
1
Order By: Relevance
“…Evidently then, through duplication and functional segregation, a number of MT isoforms emerged to support metal-ion buffering, maintaining homeostasis and protecting the host from oxidative assault. The complexity of MT evolution is readily demonstrated by differences in the MT gene clusters, copy number and functional characteristics between different species within the same genera [ 182 ]. The mouse has four MT isoforms, but numerous isoforms and subtypes/variants contribute to the heterogeneity of this family in humans; that newer proteins may line the MT queue pending annotation and functional characterization may not be a surprise.…”
Section: Discussionmentioning
confidence: 99%
“…Evidently then, through duplication and functional segregation, a number of MT isoforms emerged to support metal-ion buffering, maintaining homeostasis and protecting the host from oxidative assault. The complexity of MT evolution is readily demonstrated by differences in the MT gene clusters, copy number and functional characteristics between different species within the same genera [ 182 ]. The mouse has four MT isoforms, but numerous isoforms and subtypes/variants contribute to the heterogeneity of this family in humans; that newer proteins may line the MT queue pending annotation and functional characterization may not be a surprise.…”
Section: Discussionmentioning
confidence: 99%
“…Over them, a phylogenetic grouping of TCTPs was, according to taxonomic clustering and with a few exceptions, the same for TCTPs from molluscs that were grouped once with Vertebrata and once with Tunicata. However, the atypical clustering of Tunicata and Cephalochordata herein observed was also retrieved when other protein families were considered [ 61 ]. A derived group, incorporated within invertebrates, includes homologues from different organisms belonging to the flatworms, arthropods and nematodes.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it is possible that U. compressa contain additional MTs that differentially bind copper, zinc, and other heavy metals, as it has been predicted in [23], but the latter need to be further analyzed. In this sense, it has been shown that the equinoderm Paracentrotus livudus exhibits 7 MTs [35] suggesting that the four other potential UcMTs can be functional MTs. Thus, additional UcMTs may exist in the genome of U. compressa and these MTs will be cloned and characterized in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It is now clearly established that green and red macroalgae are more closely related among each other, and with terrestrial plants, than with brown macroalgae [32][33][34]. Green and red macroalgae belong to the kingdom Plantae, as terrestrial plants [35] whereas brown macroalgae belong to the kingdom Chromalveolta [34]. The latter is based on the observations that green and red algae contain a plastid that derive from a single event of endosymbiosis by a cyanobacteria, whereas brown algae plastids derive from a secondary or tertiary endosymbiosis event of green or red microalgae [32,33].…”
Section: Discussionmentioning
confidence: 99%